Pengembangan Strategi Komunikasi Efektif dalam Meningkatkan Kesadaran Masyarakat Tentang Pencengahan Stunting Di Desa Ajang Pulu Kecamatan Sibulue Kabupaten Bone: Pengembangan Strategi Komunikasi Efektif dalam Meningkatkan Kesadaran Masyarakat Tentang Pencengahan Stunting Di Desa Ajang Pulu Kecamatan Sibulue Kabupaten Bone - Nurul Faizah Kamaruddin; Nahdatunnisa Asry; Sulfiana (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
Stunting is a serious, urgent public health problem in Indonesia. including in Bone Regency. Stunting is a persistent nutritional problem caused by a lack of adequate nutritional intake during a child's growth period, becoming one of the serious challenges in Indonesia. Stunting can potentially cause adverse consequences on children's physical growth and thinking capacity, as well as hinder their potential to achieve maximum achievement in the future. Based on data from the Bone District Health Service, The prevalence of stunting in Ajang Pulu Village in 2022 reached 32%. This shows that serious efforts need to be made to increase public awareness about stunting prevention in the village. The high prevalence of stunting in Ajang Pulu Village is caused by several factors, among others: Lack of public knowledge about stunting , including causes, impact, and its prevention. Child feeding practices that do not comply with balanced nutrition guidelines . Lack of access to adequate health and sanitation services and weak socio-economic conditions of the community . Low public awareness of stunting has resulted in slow efforts to prevent and overcome stunting in Ajang Pulu Village. Therefore, Efforts need to be made to increase public awareness about stunting through effective communication strategies. This community service research aims to develop effective communication strategies to increase public awareness about stunting prevention in Ajang Pulu Village.